Pengaruh Sanksi Pajak Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Nurasana Nurasana; Muhammad Rivandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Tax is the main source of state income which is used to finance government expenditure and national development. The formulation of the problems studied in this study are: (1) whether tax sanctions affect individual taxpayer compliance. ( 2 ) whether taxpayer awareness affects individual taxpayer compliance. The purpose of this study was to analyze the effect of tax sanctions on taxpayer awareness on individual taxpayer compliance. The related mariable used is taxpayer compliance from taxpayers.